Population Genetic Structure and Contribution of Philippine Chickens to the Pacific Chicken Diversity Inferred From Mitochondrial DNA - Godinez, Cyrill John P.; Dadios, Peter June D.; Espina, Dinah M.; Matsunaga, Megumi; Nishibori, Masahide (Frontiers in Genetics, 2021)
The Philippines is considered one of the biodiversity hotspots for animal genetic resources. In spite of this, population genetic structure, genetic diversity, and past population history of Philippine chickens are not well studied. Phylogeny reconstruction and estimation of population genetic structure were based on 107 newly generated mtDNA complete D-loop sequences and 37 previously published sequences of Philippine chickens, consisting of 34 haplotypes. Philippine chickens showed high haplotypic diversity (Hd=0.915± 0.011) across Southeast Asia and Oceania. The phylogenetic analysis and median-joining network revealed predominant maternal lineage haplogroup D classified throughout the population, while support for Philippine-Pacific sub-clade was evident, suggesting a Philippine origin of Pacific chickens. Here, we observed Philippine red junglefowls at the basal position of the unrooted tree indicating an earlier introduction into the Philippines potentially via mainland Southeast Asia. Another observation was the significantly low genetic differentiation and high rate of gene flow of Philippine chickens into Pacific chicken population. The negative Tajima D and Fu’s Fs neutrality tests revealed that Philippine chickens exhibited an expansion signal. The analyses of mismatch distribution and neutrality tests were consistent with the presence of weak phylogeographic structuring and evident population growth of Philippine chickens (haplogroup D) in the Islands of Southeast Asia. Furthermore, the Bayesian Skyline Plot analysis showed an increase in the effective population size of Philippine chickens, relating with human settlement and expansion events. High level of genetic variability of Philippine chickens demonstrates conservation significance, thus, must be explored in the future.